(untitled) (International journal of artificial intelligence, 2026)
This article analyzes modern pedagogical methods and approaches to improving students’ speech culture in Russian language classes. The essence and content of the concept of speech culture, the factors influencing its formation, as well as communicative methods used in the educational process are highlighted. In addition, the importance of developing dialogic and monologic speech, listening activities, group work methods, and creative tasks is examined. The article also discusses the role of the teacher, criteria for assessing students’ speech, and provides practical recommendations. The research findings are significant for shaping students’ communicative competence and enhancing their culture of communication in the process of teaching the Russian language.